MODEL PEMBELAJARAN COMPONENT DISPLAY THEORY (CDT) DALAM MENINGKATKAN HASIL BELAJAR GEOGRAFI DI SMA - Brian Andreas Sayang; Fonny Rewah; Ellen Eva Poli (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2021)
The research problem is the lack of motivation and attention of students in the teaching and learning process of Geography and the Component Display Theory (CDT) model has not been applied in Syaloom Christian High School in Manado City. This study aims to determine the effect of the CDT learning model in improving learning outcomes in the Geography subjects of Syaloom Christian High School students in Manado City. The results were analyzed by statistical t-test obtained by the value of t count = 11.896 giving a recommendation that the research hypothesis is different. This value explains the differences in the learning outcomes of students in the experimental group Geography with the CDT learning model better than the control group learning outcomes without using the CDT learning model when viewed from the average value. Therefore, the CDT learning model that was applied to the experimental group students had a positive effect on improving student learning outcomes in Geography subjects.